2005
DOI: 10.1073/pnas.0502623102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the mtr operon in Methanosarcina blocks growth on methanol, but not methanogenesis, and reveals an unknown methanogenic pathway

Abstract: In the methanogenic archaeon Methanosarcina barkeri Fusaro, the N 5 -methyl-tetrahydrosarcinapterin (CH3-H4SPT):coenzyme M (CoM) methyltransferase, encoded by the mtr operon, catalyzes the energy-conserving (sodium-pumping) methyl transfer from CH 3-H4SPT to CoM during growth on H2͞CO2 or acetate. However, in the disproportionation of C-1 compounds, such as methanol, to methane and carbon dioxide, it catalyzes the reverse, endergonic transfer from methyl-CoM to H 4SPT, which is driven by sodium uptake. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
67
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 31 publications
3
67
0
1
Order By: Relevance
“…Whereas most methanogenic species grow by obligate CO 2 reduction with H 2 , methyl reduction with H 2 , aceticlastic fermentation of acetate, or methylotrophic catabolism of methanol, methylated amines, and dimethylsulfide, most Methanosarcina spp. can grow by all four catabolic pathways (49). Methanosarcina acetivorans was recently reported to grow also nonmethanogenically with CO (35).…”
mentioning
confidence: 99%
“…Whereas most methanogenic species grow by obligate CO 2 reduction with H 2 , methyl reduction with H 2 , aceticlastic fermentation of acetate, or methylotrophic catabolism of methanol, methylated amines, and dimethylsulfide, most Methanosarcina spp. can grow by all four catabolic pathways (49). Methanosarcina acetivorans was recently reported to grow also nonmethanogenically with CO (35).…”
mentioning
confidence: 99%
“…This reaction is catalyzed by the N 5 -methyl-H 4 MPT:CoM methyltransferase (Mtr), an eight-subunit membrane-bound enzyme encoded by the mtrECDBAFGH operon (10). We have demonstrated that Mtr is dispensable in M. barkeri under a variety of conditions but is required for growth via the hydrogenotrophic, aceticlastic, and methylotrophic pathways (26). Interestingly, although a ⌬mtr deletion mutant is unable to utilize methanol as a growth substrate, ⌬mtr cells are still able to oxidize methanol to CO 2 , clearly demonstrating that the Mtr-catalyzed reaction must be bypassed in M. barkeri.…”
mentioning
confidence: 99%
“…Labeling studies showed that growth on this combination of substrates occurred via a new methanogenic pathway in which acetate oxidation was used to drive methanogenic reduction of methanol. Because Mtr activity is sodium dependent, it seems possible that this pathway may be physiologically relevant in low-sodium environments (26).…”
mentioning
confidence: 99%
“…Methanosarcina is the only known genus of methanogens with members that can utilize all of the known methanogenic pathways (acetoclastic, methylotrophic, hydrogenotrophic, and methyl reducing) (71). This metabolic diversity makes these species more permissive to metabolic and genetic manipulations than other methanogens.…”
mentioning
confidence: 99%